Speech perception deficits and the effect of envelope-enhanced story listening combined with phonics intervention in pre-readers at risk for dyslexia - Vanden Bempt, Femke; Van Herck, Shauni; Economou, Maria; Vanderauwera, Jolijn; Vandermosten, Maaike; Wouters, Jan; Ghesquière, Pol (Frontiers in Psychology, 2022)
Developmental dyslexia is considered to be most effectively addressed with preventive phonics-based interventions, including grapheme-phoneme coupling and blending exercises. These intervention types require intact speech perception abilities, given their large focus on exercises with auditorily presented phonemes. Yet some children with (a risk for) dyslexia experience problems in this domain due to a poorer sensitivity to rise times, i.e., rhythmic acoustic cues present in the speech envelope. As a result, the often subtle speech perception problems could potentially constrain optimal response to phonics-based interventions in at-risk children. The current study therefore aimed 1) to extend existing research by investigating potential speech perception deficits in pre-readers at cognitive risk for dyslexia and 2) to explore the added value of a preventive auditory intervention for at-risk pre-readers, targeting rise time sensitivity, on speech perception and other reading-related skills. To obtain the first research objective, we longitudinally compared speech-in-noise perception between 28 five-year old pre-readers with and 30 peers without a cognitive risk for dyslexia during the second half of the third year of kindergarten. The second research objective was addressed by exploring growth in speech perception and other reading-related skills in an independent sample of 62 at-risk five-year old pre-readers who all combined a 12-week preventive phonics-based intervention (GraphoGame-Flemish) with an auditory story listening intervention. In half of the sample, story recordings contained artificially enhanced rise times (GG-FL_EE group, n = 31), while in the other half, stories remained unprocessed (GG-FL_NE group, n = 31) (Clinical Trial Number S60962 - https://www.uzleuven.be/nl/clinical-trial-center). Results revealed a slower speech-in-noise perception growth in the at-risk compared to the non-at-risk group, due to an emerged deficit at the end of kindergarten. Concerning the auditory intervention effects, both intervention groups showed equal growth in speech-in-noise perception and other reading-related skills, suggesting no boost of envelope-enhanced story listening on top of the effect of combining GraphoGame-Flemish with listening to unprocessed stories. These findings thus provide evidence for a link between speech perception problems and dyslexia, yet do not support the potential of the auditory intervention in its current form.